THE SUCCES OF EXCLUSIVE BREASTFEEDING IS SEEN BY HISTORY OF EARLY MARRIAGE - Aprilia Laraswati; Rize Budi Amalia; Risa Etika (UNIVERSITAS AIRLANGGA, 2022)
AbstractBackground: Early marriage is a marriage that is carried out before the bride turns to 19 years old. Tulungagung district is one of the contributors to the incidence of early marriage, which is 220 cases. The highest cases of early childhood marriage were in Kedungwaru sub-district with 37 cases. Early marriage can cause various problems, one of which is exclusive breastfeeding. Currently, the percentage of exclusive breastfeeding in Tulungagung district is 67.1%. This figure is still far from the national target. The purpose of this study was to analyze the relationship between history of early marriage and exclusive breastfeeding. Method: This research method is observational analytic with cross sectional approach. A sample of 42 respondents with the sampling technique using purposive sampling. Data were collected from June to August through a questionnaire instrument guided by interviews. The independent variable is a history of early marriage. The dependent variable is exclusive breastfeeding. Data analysis using Chi square test. Results: The results showed that respondents who were in the category of early marriage were 47.6%, and the ideal age of marriage was 52.4%, respondent with exclusive breastfeeding was 52.4% and did not give exclusive breastfeeding 47.6%. The results of the Chi square test showed a history of early marriage with exclusive breastfeeding, P value 0.087. Conclusion: Data indicates that there is no correlation between a history of early marriage to exclusive breastfeeding. Even so, early marriage must still be avoided because the impact of early marriage will cause many problems and canaffect the future of early marriage couple, even the nation and state. Keywords: Early marriage, exclusive breastfeeding, formula milk